IDENTIFIKASI DAN PEMANFAATAN JENIS UBI-UBIAN DI DESA ILMARANG KECAMATAN DAWELOR DAWERA KABUPATEN MALUKU BARAT DAYA - Wilhelmina Lekawael; Alwi Smith (Program Studi Pendidikan Biologi FKIP Unpatti, 2016)
Background: Cassava (Dioscorea sp.) Is a seasonal crop with twisted stems and forming yam. Sweet potatoes contain a large amount of carbohydrates, can be the basic ingredients of making flour, ethanol or alcohol. Method: The population in this study were 25 community-owned yams. This research conducted for 1 month from January 6 to February 6, 2016. Variable in this research is identification of type of sweet potato in Ilmarang Village. Result: Identification of 25 community gardens found 4 types of potatoes consisting of: cassava (Manihot esculenta Crants), sweet potato (Ipomea batatas L.), yam taro (Colocasia esculeata L.) and yam gembili (Diascorea esculenta L). Conclusion: Utilization of cassava as staple food of rice substitute and processed into various kinds of products such as crackers and food